Application of Therapeutic Therapy Therapies in Improving Baby Motor Development - Wita Oktaviana; Budi Anna Keliat (Universitas Muhammadiyah Semarang, 2020)
Infancy is the starting point according to the capabilities and abilities that are formed. The age of the baby has a developmental task that must be questioned, namely trust and suspicion, which is not fulfilled so that it can cause fear there will be no comfort from the environment so that this baby develops suspicion for others and does not trust other people as well. Therapeutic group therapy (TKT) is one type of therapy that helps complete the development of infants, one of which is the development of motor skills. The purpose of reporting this case is to further resolve the application of TKT in improving infant motor development. The method used in this scientific work is a case report. The intervention was carried out on six family that has babies 0-6 months with a priority nursing diagnosis that is enforced is the readiness to increase the infant's age. Interventions were carried out in groups where each group consisted of 6-10 people. Improving the ability of infants through discussion and interviews after the intervention is carried out. The interventions given were generalist therapy and therapeutic group therapy (TKT). The author uses a workbook and a therapeutic evaluation book for Therapeutic Groups (TKT) to determine the understanding of baby's abilities. The results obtained are group therapy that can provide increased motor skills in infants.